What Lawyers Could Learn from the Corporate Practice of Medicine - Melissa D. Mortazavi (Washington University Journal of Law and Policy, 2025)
Proponents of the United States’ domestic experiments in non-lawyer ownership (NLO) of legal practice justify them in terms of increasing “access to justice.” But what if opening ownership of legal practice to investment capital only exacerbates market failures (leading to further consolidation and increased costs to clients), while also compromising professional autonomy and fiduciary duty? The legal profession must be clear-eyed about who are the real winners and losers of such a shift and avoid being blinded by wishful thinking. Prominent legal scholars have repeatedly touted NLO as a solution to the access to justice crisis. However, there is scant evidence from real world to indicate whether NLO is even a partial remedy, let alone a panacea. This Article examines the corporatization of medical practice and the experiences of doctors to better understand potential pitfalls for the legal profession. It does so with a particular eye towards two questions: Who are the beneficiaries of received efficiencies or profits and what legal oversight might be effective in curbing harms to the public? This inquiry reveals that, thus far, there are no clear discernable benefits of NLO to the poor and indigent. To the extent that these systems indicate benefits, they appear to run to lawyers themselves in opening new capital fundraising opportunities and potentially to clients the middle class. Further, examination of the medical context reveals that reliance on state regulation and statutory law has been ineffective at safeguarding professional ethics concerns from the market pressures linked to increased market attention. The Article concludes that influx of non-lawyer capital is likely to increase the risk of consolidation of services which could impact negatively client access and contribute to professional autonomy disenfranchisement. Corporate ownership of legal practices is a space where risk is high and rewards, particularly in terms of access to justice, are unclear at best.
Keywords: NonLawyerOwnership; AccessToJustice; LegalProfessionEthics